The Effects of Sanctions on Iraq - Buck, Lori C. (My University, 1997)
The purpose of this thesis was to examine the impact and the effectiveness of the sanctions imposed on Iraq, and to determine whether the impact prompted Iraqi compliance with the goals of the sanctioning coalition. This thesis argues that although Iraq was an ideal target and the impact on the country was indeed calamitous, this has not induced the effects desired by the sanctioning coalition. The punitive nature of the sanctions, in conjunction with the ambitious agenda outlined by the sanctioning coalition have prevented Iraq from complying with the goals of the sanctions. By indefinitely prolonging the sanctions, the Iraqi population continues to suffer from insufficient food and medicine, while the Iraqi regime remains impervious to the sanctioning coalition's demands. The Iraqi case study has provided strong evidence that the premise underlying international economic sanctions is false; sanctions should not be imposed under the assumption that increasing the damage to the population will induce compliance.
Keywords: Political Science; Political Science